First Line and Second Line Chemotherapy in Advanced Cholangiocarcinoma and Impact of Dose Reduction of Chemotherapy: A Retrospective Analysis - Möhring, Christian; Feder, Jan; Mohr, Raphael U.; Sadeghlar, Farsaneh; Bartels, Alexandra; Mahn, Robert; Zhou, Taotao; Marinova, Milka; Feldmann, Georg; Brossart, Peter; von Websky, Martin; Matthaei, Hanno; et al. (Frontiers in Oncology, 2021)
Objective: Prognosis of patients with irresectable cholangiocarcinoma is still poor. The ABC-02 trial established the current first line (1L) standard systemic chemotherapy (CT) with gemcitabine/platinum derivate for advanced cholangiocarcinoma. However, the majority of patients needed therapy adaptions. Thus, the aim of this study was to evaluate 1L and second line (2L) therapy regimens and the impact of therapy adaptions in an unselected real-life cohort of patients with advanced cholangiocarcinoma. Materials and Methods: This is a single institution retrospective analysis of patients with irresectable cholangiocarcinoma who were treated with gemcitabine/platinum derivate from 2010 to 2018. Overall survival (OS), progression-free survival (PFS) and toxicity were analyzed for all patients, especially with regard to CT de-escalation. Results: Fifty-eight patients receiving gemcitabine/platinum derivate were included in the analysis. Median OS and PFS were 12.2 and 6.9 months. Interestingly, 41 patients (71%) needed therapy de-escalation. However, despite reduced CT exposition, there was no-significant difference in OS (10.8 months vs. 15.6 months, p = 0.127), and patients suffered from less adverse events during CT. 21 (36%) patients reached 2L CT, most often with FOLFIRI (57%). Survival beyond the end of 1L CT was 7.1 months with 2L CT vs. 2.9 months with BSC. Conclusion: In our study, the combination of gemcitabine/platinum derivate showed similar OS and PFS as randomized prospective phase II/III trials. Therapy regimen adaptions were needed in the majority of patients. However, individualized modifications of the therapy regimen allowed better tolerance as well as continuation of therapy and did not significantly influence median OS. Furthermore, our study revealed a potential survival benefit with 2L CT for selected patients.